Informações epistolares: memórias em envelopes - Andrade, Brenda Alves de (2014)
With the general objective to analyze the handwritten epistles of theSanta Claus Program of the Correios, 2009 version, as information artifact by electing the aspects of the individual and collective memory of the writers, from Paraíba, the study analyzed 243 handwritten letters that were discarded at the end of the campaign. The research adopted as theoretical perspective the studies of authors like: Deleuze and Guatari (1992) for the epistle information concept; Foucault (1992) and Gomes (2004) in the self-writing, in addition to Halbwachs (2006) for selecting the memory aspects. In relation to the methodological viewpoint, we adopted a quanti-qualitative approach in the documental research and to aid the analysis we used the theoretical assumptions of Bardin´s content analysis (1977). Firstly, we mentioned the aspects related to the construction of the epistle information concept regarding Information Science by including the epistles, in the area, as artifact of information and memory, once these are full of information that is able to reveal aspects of thought as well as representations of the society. As a result, it was verified that the information enunciations versus articulated epistles constitute a possible concept of Epistle Information. The analysis revealed the writers´ personal aspects by unveiling the individual memory of each participant and when expressed, from a general, social and collective outlook, it was possible to (re)construct the writers´ collective memory and perceive the Santa Claus Campaign of the Correios, in 2009, and its product as a construct of the social reality. Therefore, the epistles constitute meaningful information sources able to alter the knowledge on the individuals´ socioeconomic structures that compose the sample of this study.